Functional and structural organization of medial entorhinal cortex layer VI - Märt Rannap; Shinya Ohara; Janis Winterstein; Fabian C. Roth; Andreas Draguhn; Alexei V. Egorov (iScience)
Summary: Deep layers (V/VI) of the entorhinal cortex transfer hippocampal neuronal activity to downstream neocortical networks. In addition, neurons in layer VI (LVI) of the medial entorhinal cortex (MEC) project back to all hippocampal subregions and contribute to spatial coding and memory. Their role in the processing of hippocampal output signals and their interaction with LV neurons is, however, unknown. We show that spontaneously occurring hippocampal sharp wave-ripple complexes reliably propagate from area CA1 to MEC LVI. Using anterograde tracing and in vitro optogenetics, we confirm direct hippocampal projections to LVI and show that these follow a parallel dorsoventral topography. Further investigation of the MEC deep layer network revealed very sparse excitatory connections between LVI and LVb or LVI and LVa neurons in both directions. Together, our results establish organizational principles for the hippocampal-MEC LVI output circuit and suggest largely parallel signal processing through different cellular subpopulations in MEC deep layers.